Prevalence and associated factors of suicidal behavior in students of the Universidad Nacional Mayor de San Marcos, Lima-Peru - Perales, Alberto (2019)
Introduction. World Health Organization has pointed out the increasing suicidal risk in the 115 - 44 years of age. University students are inmerse in that age group risk. Objective. To estimate the prevalence of suicidal behavior and associated variables in undergraduate students of Universidad Nacional Mayor de San Marcos (UNMSM). Methodos. Transversal and analytic study. Target population: 24 118 students registered in 2015. The Suicide Behavior Questionnaire of the 2002, 2012 Mental Health National Survey, the Zung self-rated anxiety and depression scales, and the CAGE questionnaire for potential alcohol-related problems were applied to a sample of 1819 students obtained by a bietapic with probabililty proportional to size sampling procedure. Results. Life, last year, last 6 months, and last month prevalences of suicide behavior`s components of were, in that order: (i) death wish (35%; 13,9%; 11%; 5,6%); (ii) suicidal ideation (22,4%; 8,2%; 6%;3,3%); (iii) suicidal planning (17,7%; 4,4%; 3,5%; 1,6%); and (iv) suicidal attempt (11,1%; 3,7%; 2,8%; 1,4%), and higher than the prevalences of metropolitan Lima general population. Risk factors, in terms of OR and 95% CI were: being female 1,48 (1,03-2,12), depression 2,46 (1,49-4,06), anxiety 2,5 (1,38-4,6), and living in a non nuclear home 2,51 (1,70-3,72). Only 16% of the students who attempted suicide sought professional help and 21% considered repeating the attempt. Conclusions. UNMSM undergraduate students show a riskier suicide behavior tan the general population. Both for scientific reasons and moral responsibility it is highly recommended to implement intervention strategies in order to revert this trend and protect this valuable human resource.